2021
DOI: 10.1039/d1cp01529j
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation-induced negative differential resistance in graphene oxide quantum dots

Abstract: Negative differential resistance (NDR) devices have attracted considerable interest due to their potential applications in switches, memory devices, and analog-to-digital converters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…An increase in the C/O ratio increased the conductivity, allowing the rGO conductivity to be tuned [ 66 ]. Furthermore, GO displays a negative differential resistance with varying results depending on the relative humidity, air pressure, and applied voltage [ 84 ].…”
Section: Properties Of Graphene Oxide and Reduced Graphene Oxidementioning
confidence: 99%
“…An increase in the C/O ratio increased the conductivity, allowing the rGO conductivity to be tuned [ 66 ]. Furthermore, GO displays a negative differential resistance with varying results depending on the relative humidity, air pressure, and applied voltage [ 84 ].…”
Section: Properties Of Graphene Oxide and Reduced Graphene Oxidementioning
confidence: 99%
“…The fabricated novel electronic device can find application in switches and oscillators. Sharma et al [39] synthesized graphene oxide quantum dots based on graphene oxide, cysteine, and H 2 O 2 having N-type current-voltage characteristics with PVCR of 4.7. Shim et al [40] demonstrated an NDR device on the base of a phosphorene/rhenium disulfide (BP/ReS 2 ) heterojunction.…”
Section: Reviewmentioning
confidence: 99%
“…Considerable attention is paid to developing new NDR devices [21][22][23][24][25][26][27][28]30,31,33,[36][37][38][39], indicating the research topic's relevance.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations